Qualifications and Legal Enforcement of Money Cheating and Money Game Actions in Banking Transactions from the Perspective of Banking Laws - Haykal, Hassanain; Yosep Seftiadi; Gneissa Beltsazar; Safna Khaerani; Jillan Syifa (Dinasti Research, 2024)
Violations of banking regulations and principles in banking practices carried out by certain parties for personal gain, such as commissioners, directors, shareholders, and bank employees. These actions, such as channeling profits to subsidiaries, maintenance billing, credit pipelines, and credit recycling, are categorized as Money Cheating. Meanwhile, Money Game is a form of illegal investment involving unauthorized fund collection, in accordance with the Banking Law. Although both practices appear to be fraudulent crimes, it is necessary to examine whether they constitute banking crimes or financial crimes. In Indonesia, there are no regulations or studies that specifically distinguish between Money Cheating and Money Game, despite the increasing prevalence of both practices in the banking sector. This study uses a normative juridical method to qualify Money Cheating and Money Game actions based on the Banking Law. The results of the study indicate that Money Cheating can be qualified as a banking crime according to Article 49 paragraph (1) of the Banking Law, while Money Game involves the application of several legal rules such as Article 46 paragraph (1) of the Banking Law, Article 378 of the Criminal Code, and Articles 3, 4, and 5 of the Anti-Money Laundering Law. In conclusion, both practices are serious criminal offenses that require strict legal sanctions to maintain the integrity of the banking system.